Sergio Serulnikov. "Subverting Colonial Authority: Challenges to Spanish Rule in Eighteenth Century Southern Andes". Durham and London: Duke University Press, 2003. - Guzmán Morales, Rodolfo (Fronteras de la historia, 2005)
.